Kejahatan dalam Perspektif Filsafat Proses Whitehead - Joko Siswanto (Jurnal Filsafat "WISDOM", 2000)
The purpose of this research is to inventory, describes, and critical analysis the nature evil of Whitehead's Process Philosophy.This research is pure library study. Data are collected from Whitehead's works. Philosophical-hermeneutics is usen in this research, namely, descriptive, comparative, and reflective.The results of this research are as follows:1. Evil is not "res" or a primordially entity. Evil parasitism (something adhere and destruction) goodness. Evil means nothing goodness.2. Evil is not a subjective or objective quality, but is relative and inter-relation quality. A something can be categorized as an evil or not, depend on the patterns of experience of the actual-entity society.3. Evil exist if the actual entity into unfication find suffering. This suffering is caused by degradation, destruction, and cross purpose.4. There are three ways to solve: triviality, aesthetics, and re-adjusment.5. Evil was regarded as an internal-inconsistency while God as Alpha-Omega does not know it. The nature of God is self-consistent.